2011
DOI: 10.1177/0300985811409253
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Those Histopathologic Parameters Predictive of Invasion of the Lymphatic System by Canine Mammary Carcinomas

Abstract: The aim of the present study was to determine which histopathologic parameters of primary canine mammary carcinomas (CMCs) could predict metastatic spread via the lymphatic system. A modification of the World Health Organization classification was applied to 245 CMCs. In addition to tumor subtype, neoplastic infiltration of the surrounding mammary stroma, vasculogenic mimicry, and micropapillary pattern were evaluated, and 2 histologic grading systems were used for each sample. A statistical analysis was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 44 publications
8
75
2
5
Order By: Relevance
“…13 A retrospective study comparing both the Misdorp and Peña grading systems on a large series of canine malignant mammary neoplasms was recently published. 30 This previous study showed that both histological grading systems are significant predictors (P < .001) of the risk of lymphatic vessel invasion and regional lymph node metastases at the time of diagnosis. However, the Peña system (partially published as Clemente et al 3 ) has been shown to have a better predictive ability.…”
mentioning
confidence: 90%
“…13 A retrospective study comparing both the Misdorp and Peña grading systems on a large series of canine malignant mammary neoplasms was recently published. 30 This previous study showed that both histological grading systems are significant predictors (P < .001) of the risk of lymphatic vessel invasion and regional lymph node metastases at the time of diagnosis. However, the Peña system (partially published as Clemente et al 3 ) has been shown to have a better predictive ability.…”
mentioning
confidence: 90%
“…No presente relato, o carcinoma tubular, desde o primeiro diagnóstico já apresentava características de malignidade, como a metástase em linfonodo inguinal. Rasotto et al (2012) verificaram que 60% dos carcinomas tubulares apresentaram invasão linfática e 27% metástase em linfonodos.…”
Section: Resultsunclassified
“…De acordo com Rasotto et al (2012) os carcinomas tubulares são mais frequentemente do tipo II (62%). Carcinomas tubulares grau II apresentam invasão linfovascular em 71% dos casos e metástase para os linfonodos em 31% dos casos.…”
unclassified
“…Chez la chienne, la fréquence de l'embolisation lymphatique varie aussi selon les auteurs : elle est de 25% dans une cohorte de 84 cas (De Las Mulas et al 2005) et de 38% parmi 29 cas rapportés par Millanta et al (2006), elle atteint 55% sur 102 cas (Gama et al 2008) et 78% dans une cohorte de 245 cas (Rasotto et al 2012). Dans une cohorte rétrospective des 350 carcinomes mammaires invasifs canins de notre Unité de recherches, la fréquence de l'embolisation lymphatique déterminée par HES est de 49% (171/350), c'est-à-dire une fréquence similaire à celle observée chez la chatte (communication personnelle).…”
Section: Fréquence De L'embolisation Lymphatiqueunclassified